Cyclist route assessment using machine learning - Caetano, Alan Nunes (My University, 2023)
Increasing the number of bike commutes can provide numerous benefits for individuals and communities. However, several factors including the availability of cycle paths, traffic characteristics, and pavement quality, can either encourage or discourage the use of bicycles. To promote cycling and understand how cyclists interact with the urban environment, it is crucial to assess the quality of cyclist routes. This thesis proposes an automatic assessment tool that uses machine learning to detect features of the route segment and calculates a score representing the level of safety and comfort for cyclists. The models are trained on YOLOv5 to classify pavement types, detect pavement defects and detect the presence of cycle paths. Two datasets were built and annotated for the pavement type classification and cycle infrastructure detection tasks. A questionnaire was applied to cyclists to compare the real perceptions with the automatic assessment. The results showed a good alignment with the real perceptions, validating the approach, but also demonstrated the need of adding new features and improving the models’ performance before being adequate for real use.

Aumentar o número de deslocamentos de bicicleta pode trazer inúmeros benefícios para indivíduos e comunidades. No entanto, vários fatores, incluindo a disponibilidade de ciclovias, características do tráfego e qualidade do pavimento, podem encorajar ou desencorajar o uso de bicicletas. Para promover o ciclismo e entender como os ciclistas interagem com o ambiente urbano, ´e crucial avaliar a qualidade das rotas dos ciclistas. Esta tese propõe uma ferramenta de avaliação automática que usa aprendizado de máquina para detectar características do segmento de rota e calcula uma pontuação que representa o nível de segurança e conforto para os ciclistas. Os modelos são treinados no YOLOv5 para classificar os tipos de pavimento, detectar defeitos no pavimento e detectar a presença de ciclovias. Dois datasets foram construídos e anotados para as tarefas de classificação do tipo de pavimento e detecção de infraestrutura ciclável. Foi aplicado um questionário aos ciclistas para comparar as percepções reais com a avaliação automática. Os resultados mostraram um bom alinhamento com as percepções reais, validando a abordagem, mas também demonstraram a necessidade de adicionar novas características e melhorar a performance dos modelos antes de ser adequado para uso real.
Keywords: Cyclist safety assessment; Computer vision; Deep learning